2018
DOI: 10.3390/nu10030313
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Are Associated with Cardiovascular and Cancer Mortality among Swiss Adults in a Census-Linked Cohort

Abstract: Defining dietary guidelines requires a quantitative assessment of the influence of diet on the development of diseases. The aim of the study was to investigate how dietary patterns were associated with mortality in a general population sample of Switzerland. We included 15,936 participants from two population-based studies (National Research Program 1A (NRP1A) and Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA)—1977 to 1993) who fully answered a simplified 24-h dietary recall. Mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 51 publications
(63 reference statements)
4
23
0
Order By: Relevance
“…In the current study, 11 out of 12 potential determinants of diet quality were found to be significantly associated with one or both diet quality scores. As already reported from many previous studies [13,15,24,25,28,42,45], a higher diet quality was observed for females and older participants. The weak significant association between sex and MDS in the present study was most likely due to the use of sex-specific medians in the calculation of the score.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the current study, 11 out of 12 potential determinants of diet quality were found to be significantly associated with one or both diet quality scores. As already reported from many previous studies [13,15,24,25,28,42,45], a higher diet quality was observed for females and older participants. The weak significant association between sex and MDS in the present study was most likely due to the use of sex-specific medians in the calculation of the score.…”
Section: Discussionsupporting
confidence: 84%
“…In Switzerland, the effects of sociodemographic and lifestyle factors on diet quality have been investigated in different studies [20,24,25,26,27,28,29,30]. However, since no nutrition survey existed in Switzerland until 2015, most of these results relied on undetailed dietary data or were derived from a single city or region [20,24,25,26,28,29,30]. To fill this gap, the first Swiss National Nutrition Survey menuCH was recently conducted with the aim to assess the dietary habits in a representative sample of the Swiss population [27,31].…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that the "salt adherent" cluster members are notably heavier in habit of adding additional salt at the table, but they are also highly aware of their excessive salt use and significantly less attentive in limiting their salt consumption. Studies suggest that general changes in dietary habits are needed for an effective decrease in salt content to affect NCD risks [90][91][92]. A survey by Mørk et al [74] showed that consumers who have already changed their dietary salt intake or intend to do so are also more willing to purchase salt-reduced food products.…”
Section: Discussionmentioning
confidence: 99%
“…In most longitudinal studies, however, dietary assessment occurs once at study entry (i.e., potentially decades before the end of the study); thus, the DALYs-dietary patterns association calculated based on this information reflects the impact of "old" dietary habits on morbidity and mortality [9]. Although this information is extremely valuable from a public health perspective, the impact of currently consumed diets on DALYs may be more relevant to improve and dynamically adapt nutritional guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, we combined two chronologically distinct data sources in order to calculate the association between dietary patterns currently consumed and DALYs from NCDs. In this method, a recent cross-sectional study was first used to characterize the currently consumed dietary patterns [11][12][13], whereas a prospective cohort study was used to quantify the dietary patterns-DALYs association for individuals who consumed a diet similar to the modern dietary patterns [9]. This approach extends previous work on the estimation of DALYs in cohort studies to the calculation of the association between current dietary patterns and DALYs.…”
Section: Introductionmentioning
confidence: 99%